PENGEMBANGAN METODE PEMASARAN DAN SISTEM MANAJEMEN BAGI PELAKU USAHA MAKANAN TERDAMPAK PANDEMIK COVID 19 - Erlynda Yuniarti Kasim; Dwi Rahmawati (Jurnal Berdaya Mandiri, 2021)
Since the Covid-19 pandemic hit the world, the lifestyle of Asia, especially Indonesia, underwent extraordinary changes at the beginning of 2020. On a national and global scale, the decline in activity and economic growth resulted in a decline in public demand, including products and services produced by MSMEs. . Apart from that, partners also have limitations in managing and classifying income and expenses in terms of financial records. Taking into account the global Covid-19 pandemic, Indonesia has disrupted daily life due to social distancing and government housing regulations, which have an impact on the MSME industry. The main challenge faced by MSMEs is declining demand. Compared to normal conditions, this also reduces the impact of limited MSME operations and direct consumer spending. MSMEs can achieve several things, such as utilizing e-commerce sales, improving service quality, digital marketing, and customer relationship marketing. Taking into account the situation mentioned in the previous section and the latest information provided by the Indonesian Central Statistics Agency regarding economic growth of -5.32% in the second quarter of 2020. For this reason, the proposer considers it necessary to conduct a study and implementation of the Community Partnership Program (PKM), especially in East Jakarta City area whose people are affected by the crisis during the pandemic. The most significant impact is that after being registered with an online food delivery service, there is an increase in sales from the usual 20 â€“ 30 percent per day.Â